Personalized 2D color maps. (October 2016) - Waldin, Nicholas; Bernhard, Matthias; Rautek, Peter; Viola, Ivan
Abstract: 2D color maps are often used to visually encode complex data characteristics such as heat or height. The comprehension of color maps in visualization is affected by the display (e.g., a monitor) and the perceptual abilities of the viewer. In this paper we present a novel method to measure a user׳s ability to distinguish colors of a two-dimensional color map on a given monitor. We show how to adapt the color map to the user and display to optimally compensate for the measured deficiencies. Furthermore, we improve user acceptance of the calibration procedure by transforming the calibration into a game. The user has to sort colors along a line in a 3D color space in a competitive fashion. The errors the user makes in sorting these lines are used to adapt the color map to his perceptual capabilities. Abstract : Graphical abstract: Abstract : Highlights: A personalization of 2D color maps to individuals with color vision deficiencies. Measurements based on a game for increased enjoyment. Novel method for altering color maps for any personalization method.